Forgiveness Mediates the Protective Role of Religiosity on Psychological Distress: Findings from Inmates in Eswatini Correctional Centres - Olawa, Babatola D. (Journal of religion and health, 2022)
This study examined the mediating role of forgiveness in the relationship between religiosity and psychological distress among 244 inmates (Meanage = 31.6) in Eswatini, a country in Southern Africa formerly called Swaziland. Results showed that religiosity, forgiveness and psychological distress were related in the expected direction. Outcomes of SEM analyses indicated that high religiosity was associated with greater forgiveness, which in turn associated with low distress. While the presence of positive feelings of forgiveness was a significant mediator, the absence of negative feelings was not. Psychotherapeutic techniques targeting lower distress from religiosity should utilize forgiveness interventions with a special focus on the presence of positive feelings toward the offender.